Family communication patterns and school dropout intention: The mediating role of academic resilience among Cambodian high school students - Ramasa Varity (Journal of Education, Social & Communication Studies, 2026)
Family communication patterns play a critical role in shaping adolescents’ educational experiences and decisions. This study examines the relationship between family communication patterns and school dropout intention, with particular emphasis on the mediating role of academic resilience among high school students in Cambodia. A quantitative survey was conducted with 243 students selected through simple random sampling, measuring conversation orientation, conformity orientation, academic resilience, and school dropout intention. The findings reveal that family communication patterns significantly influence both academic resilience and students’ intention to leave school. Academic resilience mediates the relationships between both dimensions of family communication patterns and school dropout intention, highlighting its role as a key psychological mechanism linking family communication processes to educational outcomes. This study extends the application of family communication patterns theory by demonstrating its relevance in a non-Western, collectivist context and by integrating academic resilience as a mediating construct. It further underscores how culturally embedded family communication practices shape students’ capacity to persist in school. The findings offer interdisciplinary insights for education, social, and communication research, while providing practical implications for educators, policymakers, and families in addressing school dropout intention through strengthened communication and resilience-building strategies.